PENEGAKAN HUKUM TINDAK PIDANA KORUPSI BERDASARKAN ASAS DUE PROCESS OF LAW: Studi Komparasi Kejaksaan RI dan KPK - Reyhan Harits Abimanyu, (2021)
Corruption is a destructive and complex crime. Eradicating corruption is not only by punishing the perpetrators, but it requires an effective law mechanism. The author raises the comparison of the application of the Principle of Due Process of Law in law enforcement of corruption by Kejaksaan RI and KPK, the role of each institution, and the effectiveness of the Law on the Kejaksaan RI and KPK. Based on ICW statistical data, in 2020 KPK and Kejaksaan RI, both Corruption Eradication Commission and Kejaksaan RI, will only apply Law No. 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering against 20 with a total of 1,298 defendants. This research is normative juridical research, namely legal research conducted by examining library materials using literature study objects, then supported by primary data through interviews. This research was conducted with a comparative approach that adheres to descriptive qualitative research. Based on data from Transparency International Indonesia, one of the obstacles seen in the indicators of the Accountability and Integrity dimensions related to the application of the due process of law that investigators complained about was the special treatment of witnesses and the warrant of unapproved witnesses. Keywords: Corruption, Prosecutor's, KPK, Effective, Fair trial.